2022
DOI: 10.3389/fcell.2021.792597
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Brachytherapy vs. External Beam Radiotherapy on Sexual Function in Patients With Clinically Localized Prostate Cancer: A Meta-Analysis

Abstract: Purpose: The aim of this study was to compare the effect of brachytherapy (BT) versus external beam radiotherapy (EBRT) on sexual function in patients with localized prostate cancer (PCa).Methods: Data were retrieved from the PubMed, Cochrane Library, Embase, China National Knowledge Infrastructure (CNKI), and Wanfang Database until March 4, 2021. Analysis was performed by using RevMan 5.4.1. The main clinical outcomes were the Prostate Cancer Symptom Indices (PCSI) scale and the Expanded Prostate Cancer Index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Functionally, our data indicate that BRI cancelled the TGF-β2-induced decrease in maximal mitochondrial respiration. It is known that TGF-β2 induces cellular metabolic reprograming and redox status, which is associated with cellular properties [ 27 ]. Indeed, we recently found that TGF-β2 shifts energy reserves from the mitochondria to glycolysis in both 2D and 3D HTM cells [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Functionally, our data indicate that BRI cancelled the TGF-β2-induced decrease in maximal mitochondrial respiration. It is known that TGF-β2 induces cellular metabolic reprograming and redox status, which is associated with cellular properties [ 27 ]. Indeed, we recently found that TGF-β2 shifts energy reserves from the mitochondria to glycolysis in both 2D and 3D HTM cells [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, an increasing number of novel 225 Ac-labeled compounds are currently under development. We last counted 16 Current production levels are listed for current sources, while values for potential sources list estimates of maximum possible production at sample of existing and operational facilities that have dedicated stations for large-scale medical isotope production. This list includes key facilities but is not exhaustive and does not include potential yet currently impractical methods that may be established in the future.…”
Section: Thorium 227mentioning
confidence: 99%
“…High-dose-rate brachytherapy temporarily introduces iridium isotopes close to the tumor site to deliver a higher dose of radiation over a shorter period of time and overcomes limitations of early brachytherapy approaches ( 14 ). Evidence-based medicine indicates that brachytherapy may be superior to EBRT in terms of efficacy and safety in several patient groups ( 15 , 16 ). Survival rates are remarkable: 17-years survival of 97% in prostate cancer ( 17 ); 79.4% 3-years survival in cervical cancer patients ( 18 ).…”
Section: Section 1: Historical Contextmentioning
confidence: 99%
“…Prostate cancer (PCa) is the second most frequently observed neoplasia (after lung cancer) in males worldwide [ 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…As screening for prostate cancer has increased in the past few decades, prostate cancer has generally been detected at an earlier stage and in younger patients. As treatment has also been refined, with more patients surviving longer, quality of life concerns have become central [ 2 , 8 , 19 ].…”
Section: Introductionmentioning
confidence: 99%